(3CfehPL GddHjH aj NUGFU GdMHjHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CJbf HMceJg cd TF hSejJg CfehPL GddHjH ai NUGFU GdMHjH GdHGH GdChd ai GdNUGFU GdJi ajgG LejY s
(3BNQgG (B:s
(3hcPdc SejJ GdRgQGA hGddg JYGdi CYde GfJgi HMeO Gddg hcai hSdGe Ydi YHGOg GdPjf EUWai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(1100 d) s
Keywords: (3GdeLGejYs